#### Answer

(C'∩A) U (C'∩B') = {a,g,h}

#### Work Step by Step

U={a,b,c,d,e,f,g,h}
A={a,g,h}
B={b,g,h}
C={b,c,d,e,f}
To find (C'∩A) U (C'∩B'), we need to find B' and C'.
B' represents all the elements of U which are not in B
So, B'={a,c,d,e,f}
C' represents all the elements of U which are not in C
So, C'={a,g,h}
Now, C'∩A={a,g,h} ∩ {a,g,h} ={a,g,h}
(List of all common elements in C' and A )
Now, C'∩B'={a,g,h} ∩ {a,c,d,e,f} ={a}
(List of all common elements in C' and B' )
(C'∩A) U (C'∩B') = {a,g,h} U {a} = {a,g,h}
(List of all elements of (C'∩A) and the elements of (C'∩B') which are not present in (C'∩A))